Ablative, Endovascular, and Biliary Interventions for Patients with Pancreatic Cancer - Hevert, Elizabeth Anne C.; Howser, Collin G.; Gould, Michael L.; Brown, Daniel B. (Seminars in Interventional Radiology, 2019)
Interventional radiologists have multiple points of involvement in the treatment and management of patients with pancreatic adenocarcinoma. There is increasing interest in cytoreductive treatment of the primary tumor as well as metastatic disease via arterial and ablative techniques. The focus of this article is on the current evidence for pancreatic irreversible electroporation. For patients undergoing curative surgery or terminal palliation, interventional radiology can manage complications and symptoms. In this article, therapeutic and palliative options in this group of patients including postoperative embolization, biliary drainage, and stent placement are reviewed.
Keywords: pancreatic adenocarcinoma; irreversible electroporation; radioembolization; biliary drainage; embolization; interventional radiology